Between the norm and a hard place: representing marginality in Harmony Korine's Gummo - De Villiers, Jacques (Centre for Film and Media Studies, 2015)
This dissertation centres on an examination of Gummo, the provocative directorial debut by filmmaking enfant terrible, Harmony Korine. While largely dismissed by critics who were put off by the film's visceral intensity, unconventional narrative structure and unsentimental depictions of marginality, I want to counter such criticism by arguing that Gummo in fact offers a refreshingly new approach to cinematic representations of white poverty in the United States. While U.S. cinema has often furnished us with representations of poverty, the majority of these ï¬ lms have tended to focus on characters' economic hardships. By contrast, Gummo is almost unique in privileging the cultural and ideological dimensions - concerns with weight and sporting success, attaining and retaining certain norms of masculine strength and appearance, repeated references to celebrity culture, to name but a few examples - while locating such normative dimensions within the bleak material realities that mark life on the breadline. In so doing, Gummo draws attention to the paradoxical cultural question of poverty in the so-called First World: How does one engage with the daily barrage of ideologically imposed social and cultural norms when one's basic living conditions are diametrically opposed to such norms? While most films tend to treat the poor as always outside and in binary opposition to the normative order, I want to propose that we re-think poverty and marginality's cultural identity as always hybrid and in-between the margin and the norm. Such an interstitial position is articulated by Gummo's highlighting of two very different representational approaches: one based on an abject materiality that is often framed in an almost tactile and disconcertingly visceral manner, the other relying on the maintenance of a plastic or surface aesthetic through which symbolic cultural norms and ideals are semiotically conveyed. Rather than seeking to resolve such approaches' contradictions to one another, Gummo gives cinematic expression to the ambivalent position that results when one occupies both spaces simultaneously. This encourages us to think of marginality interstitially, rather than conceiving of it as merely 'other' to what is considered normative or mainstream. In theorising Gummo's representation of white marginality as an interstitial phenomenon, I have drawn primarily on the work of three quite different thinkers: post-colonial theorist Homi K. Bhabha, gender theorist Judith Butler and film theorist Vivian Sobchack. Chapter one engages with Bhabha's ideas about cultural hybridity, seeking to demonstrate how Gummo represents marginality as a decidedly heterogeneous affair, one that blurs all clear notions of centre and margin. Chapter two explores this breaking down of binary value further by investigating how, through subversive acts of re-signification, the norm or centre can become 'contaminated' by the margin. Here I employ Butler's notion of performativity and citation, which demonstrates how norms can be materialised and cited in non-normative circumstances that challenge the validity of the dominant discourse. Such 'non-normative' materialisation blurs the boundary between that which is normative and that which is 'other'. Chapter three expands this notion of re-signiï¬ cation and hybridity still further. Drawing upon the phenomenology-based theory of Vivian Sobchack, I explore those aspects of Korine's film that - like Sobchack's theory - privilege materiality and the body as sites of experience. I then proceed to read Sobchack in relation to Butler and Bhabha, arguing that the manner in which Korine almost tactically frames the harsh, abject materiality of Gummo's setting plays off and meshes with the presence of symbolic norms and ideals. Gummo and its characters are thus ï¬ rmly lodged in a hybrid Third Space; in-between the cultural signs of 'normalcy' and a materialised space of messy abjection. It is between these two seemingly incompatible dimensions that the film and its characters make meaning and forge a sense of cultural identity.